2004
DOI: 10.1007/s00421-004-1188-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake kinetics and maximal aerobic power are unaffected by inspiratory muscle training in healthy subjects where time to exhaustion is extended

Abstract: The aim of this study was to determine whether 4 weeks of inspiratory muscle training (IMT) would be accompanied by alteration in cardiopulmonary fitness as assessed through moderate intensity oxygen uptake (V(.)O(2)) kinetics and maximal aerobic power (V(.)O(2max)). Eighteen healthy males agreed to participate in the study [training group (Tra) n=10, control group (Con) n=8]. Measurements of spirometry and maximal static inspiratory mouth pressure ( PI(max)) were taken pre- and post-training in addition to: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
47
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 28 publications
16
47
0
1
Order By: Relevance
“…Also the results of this study coincided with the results achieved by Edwards and Cooke,2008 17 who concluded that the inspiratory muscle training device had a significant effect on maximum inspiratory pressure in patients underwent pulmonary lobectomy.…”
Section: A Study Results Achieved By Hamad 2012supporting
confidence: 77%
“…Also the results of this study coincided with the results achieved by Edwards and Cooke,2008 17 who concluded that the inspiratory muscle training device had a significant effect on maximum inspiratory pressure in patients underwent pulmonary lobectomy.…”
Section: A Study Results Achieved By Hamad 2012supporting
confidence: 77%
“…In the case of constant-load exercise tests sustained to the limit of tolerance, the improvements are larger, typically greater than 30% for tests lasting 13 to 20 min (50,180). For higher intensity, shorter duration tests, the improvements are correspondingly smaller, about 4% to 13% for tests lasting 3 to 4 min (50,141).…”
Section: Ergogenic Effects Of Respiratory Muscle Trainingmentioning
confidence: 96%
“…As Ray, Pendergast, and Lundgren [30] proved that the resistance respiratory muscle training on nine males divers for four weeks (30 min per day, 5 days per week) improved the MVV significantly. In contrast, Edwards and Cooke [31] stated that there was no change in MVV parameter on 18 males between both POWERbreath group (PG=10), the control group (CG=8) and even within the group itself. This could be referred to the low load used in their study, which was only 15% of the MIP.…”
Section: Discussionmentioning
confidence: 88%